"Authentic Alignment" – a new framework of entrepreneurship education. Issue 9 (10th October 2016) - Macht, Stephanie Alexandra; Ball, Steve
Abstract : Purpose: This paper seeks to address an underdeveloped aspect of entrepreneurship education (EE), which is still criticised for not explicitly linking educational practice with established educational theory. As such, the purpose of this paper is to propose a novel educational framework – Authentic Alignment – that the authors evolved based on their own EE practice, as well as two major educational theories. Design/methodology/approach: A review of a range of conceptual educational frameworks in EE revealed a gap in the current literature, referring to the fact that practice is not sufficiently linked to sound educational theory. The paper combines a range of educational theories – predominantly Constructive Alignment (CA) and Authenticity – to develop a novel conceptual framework, termed "Authentic Alignment". The discussion of Authentic Alignment draws upon EE literature, as well as student feedback and the reflections and experiences of the practitioners and academics involved in delivering a higher education unit underpinned by Authentic Alignment. Findings: It is argued that Authentic Alignment coherently and explicitly links educational practice to major established educational theories and as such presents a valuable approach to education through entrepreneurship as it aligns authentic approaches to instruction, learning and assessment that strike a balance between resembling and being relevant for real entrepreneurial activity. Practical implications: The paper invites educators to draw upon Authentic Alignment for their own entrepreneurship units/programmes by customising the specific approaches to their own requirements, while retaining the underlying principle of constructively aligned authentic education. Originality/value: By explicitly linking EE to CA and Authenticity, this paper introduces a novel educational framework that provides a valuable structure for education through entrepreneurship. The customisability of Authentic Alignment, however, suggests a wider applicability and is thus valuable also for education about and for entrepreneurship.